Clinical evaluation of two prosthetic suspension systems in a bilateral transtibial amputee - Gholizadeh, Hossein; Abu Osman, Noor Azuan; Kamyab, Mojtaba; Eshraghi, Arezoo; Luviksdottir, Asa Gulaug; Wan Abas, Wan Abu Bakar (Lippincott, Williams & Wilkins, 2012)
The effects of Seal-In X5 and Dermo liner (Össur) on suspension and patient's comfort in lower limb amputees are unclear. In this report, we consider the case of a 51-yr-old woman with bilateral transtibial amputation whose lower limbs were amputated because of peripheral vascular disease. The subject had bony and painful residual limbs, especially at the distal ends. Two prostheses that used Seal-In X5 liners and a pair of prostheses with Dermo liners were fabricated, and the subject wore each for a period of 2 wks. Once the 2 wks had passed, the pistoning within the socket was assessed and the patient was questioned as to her satisfaction with both liners. This study revealed that Seal-In X5 liner decreased the residual limb pain experienced by the patient and that 1-2 mm less pistoning occurred within the socket compared with the Dermo liner. However, the patient needed to put in extra effort for donning and doffing the prosthesis. Despite this, it is clear that the Seal-In X5 liner offers a viable alternative for individuals with transtibial amputations who do not have enough soft tissue around the bone, especially at the end of the residual limb.